Kemampuan Peserta Didik dalam Menulis Karangan Narasi Kelas IV Sekolah Dasar - Ferdinal, Hanafa Putri; Sari, Rezi Novita; Chandra, Chandra; Wijanarko, Tiok (Lembaga Yasin AlSys, 2024)
This research aims to determine students' abilities in writing narrative essays in class IV elementary school. This research uses a suggestive narrative essay type. In this research, researchers used a qualitative approach. The subjects to support this research were one class IV student in one of the elementary schools. The instrument the researchers used was the instrument for students' ability to write narrative essays. Apart from that, the data analysis technique used is descriptive data analysis technique, which describes a condition as it is. Based on the results of the analysis of the ability of fourth grade elementary school students in writing narrative essays, it can be concluded that there are three of the five aspects that are considered inappropriate.